Construction of a comprehensive nutritional index and its correlation with quality of life and survival in patients with nasopharyngeal carcinoma undergoing IMRT: A prospective study. (November 2019) - Deng, Jun; He, Yan; Sun, Xue-Song; Li, Jian-Mei; Xin, Ming-Zhu; Li, Wen-Qiong; Li, Zhen-Xiu; Nie, Shan; Wang, Cong; Li, Yan-Zhu; Chen, Li-Ping; Chen, Lin-Min; et al.
Highlights: 359 NPC patients were involved from 2011 to 2014 and were followed up to March 2019. CNI was constructed to reflect integrated nutrition status and was appropriate in NPC patients. ETORC QLQ-C30 and QLQ-H&N35 was combined to assess the QoL detailed at three points. Lower CNI correlated worse QoL and OS, CNI was an independent prognostic factor of OS. Abstract: Objectives: The aim of this study was to investigate the relationship between a comprehensive nutritional index (CNI) and QoL in patients with NPC who undergo IMRT and to explore the relationship between CNI and survival. Methods: 359 patients with newly diagnosed NPC were enrolled. QoL was assessed with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 and Quality of Life Questionnaire Head and Neck Cancer Module at three time points: before, immediately after, and 3 months after IMRT. The CNI comprised five values including body mass index, usual body weight percentage, hemoglobin, albumin, and total lymphocyte count, and was evaluated before and immediately after IMRT. The correlation between the CNI and QoL and the effect of CNI on prognosis were analysed. Results: QoL and CNI scores decreased remarkably after IMRT (P < 0.05). The CNI was quite low in patients with III–IV clinical tumor stage and those undergoing induction chemotherapy plus concurrent chemotherapy. After IMRT, lower CNI score correlated worse QoL (P < 0.05). The Kaplan-Meier curve indicated that patients with lower CNI had significantly poorer survival outcomes (P = 0.02). In multivariate analysis, CNI remained an independent prognostic factor of overall survival (P = 0.046). Conclusions: CNI can be recommended as an appropriate indicator reflecting the integrated nutrition status of NPC patients. Low CNI was associated with poor QoL and predicted a poor survival outcome. More interventions should be taken to improve the nutrition status of NPC patients to improve QoL and enhance survival outcomes.